Triple axis : Iran's relations with Russia and China - Esfandiary, Dina; Tabatabai, Ariane (Library of international relations (Series), 2018)
The most significant challenge to the current international order is the growing power of ambitious states opposed to the West. Iran, Russia and China each view the global structure through the prism of historical experience. Rejecting the universality of Western liberal values, these states and their governments see the relative decline of Western economic hegemony as an opportunity. Yet cooperation between them remains fragmentary. Dina Esfandiary and Ariane Tabatabai here address this 'triple axis' in the realms of energy, trade and military security. In particular, they scrutinise Iran-Russia and the often-overlooked field of Iran-China relations. Their argument - that interactions between the three will shape the world stage for decades to come - will be of interest to anyone looking to understand the contemporary international security puzzle.